Ethnic penalties and hiring discrimination: comparing results from observational studies with field experiments in the UK - Zwysen, W; Di Stasio, V; Heath, A (SAGE Publications, 2020)
Ethnic minorities fare less well on average in the labour market than their white British counterparts. Experimental research shows that employers discriminate against ethnic minority applicants while hiring, but it is impossible to say from these studies how much of minorities’ overall disadvantage – which reflects compositional differences and search behaviour as well as hiring – is due to discrimination. This article connects results from two UK-based field experiments with ethnic penalties estimated from comparable samples of the UK Labour Force Survey and Understanding Society to show the relation between hiring discrimination and labour market penalties, for several ethnic minority groups. Higher hiring discrimination is indeed associated with worse ethnic employment penalties, but similarly discriminated against groups do not necessarily face the same ethnic penalties. We provide a discussion of possible reasons for this variation. Our research points to socio-economic resources and supply-side differences among ethnic groups as plausible explanations.